Antithrombin Concentrates Use in Children on Extracorporeal Membrane Oxygenation: A Retrospective Cohort Study. Issue 3 (March 2015) - Wong, Trisha E.; Delaney, Meghan; Gernsheimer, Terry; Matthews, Dana C.; Brogan, Thomas V.; Mazor, Robert; McMullan, D. Michael; Reiner, Alex P.; Konkle, Barbara A.
Abstract : Objective: To investigate whether receipt of any antithrombin concentrate improves laboratory and clinical outcomes in children undergoing extracorporeal membrane oxygenation for respiratory failure during their hospitalization compared with those who did not receive antithrombin. Design: Retrospective cohort study. Setting: Single, tertiary-care pediatric hospital. Patients: Sixty-four neonatal and pediatric patients who underwent extracorporeal membrane oxygenation for respiratory failure between January 2007 and September 2011. Intervention: Exposure to any antithrombin concentrate during their extracorporeal membrane oxygenation course compared with similar children who never received antithrombin concentrate. Measurements and Main Results: Thirty patients received at least one dose of antithrombin during their extracorporeal membrane oxygenation course and 34 patients did not receive any. The median age at admission was less than 1-month old. Age, duration of extracorporeal membrane oxygenation, or first antithrombin level did not differ significantly between the two cohorts. The mean plasma antithrombin level in those who never received antithrombin was 42.2% compared with 66% in those who received it. However, few levels reached the targeted antithrombin level of 120% and those who did fell back to deficient levels within an average of 6.8 hours. For those who received antithrombin concentrate, heparin infusion rates decreased by an average of 10.2 U/kg/hr for at least 12 hours following administration. No statistical differences were noted in the number of extracorporeal membrane oxygenation circuit changes, in vivo clots or hemorrhages, transfusion requirements, hospital or ICU length of stay, or in-hospital mortality. Conclusions: Intermittent, on-demand dosing of antithrombin concentrate in pediatric patients on extracorporeal membrane oxygenation for respiratory failure increased antithrombin levels, but not typically to the targeted level. Patients who received antithrombin concentrate also had decreased heparin requirements for at least 12 hours after dosing. However, no differences were noted in the measured clinical endpoints. A prospective, randomized study of this intervention may require different dosing strategies; such a study is warranted given the unproven efficacy of this costly product. Abstract : Supplemental Digital Content is available in the text.